The effects of natural additives on litter condition, microclimate environment and antimicrobial resistance in the broiler chickens rearing - Dančová, Nikola; Gregová, Gabriela; Szabóová, Tatiana; Marcinčák, Slavomír (Frontiers in Sustainable Food Systems, 2025)
IntroductionFeed additives like humic substances (HS) and probiotics (P) can enhance broiler health, production, welfare, and environmental conditions.MethodsThis study involved 120 one-day-old ROSS 308 broiler chicks divided into three groups for a 39-day fattening period. The first experimental group (HS) received a feed mixture with 0.6% HS; the second group (HS + P) got the same HS concentration along with a probiotic strain (Limosilactobacillus fermentum) in water. The control group (C) was fed a basal diet without additives. The HS mixture was also added to the litter in both the HS and HS + P groups, whereas the C group did not receive any HS. The study examined the effects of HS as litter additives on the physical– chemical properties of poultry litter and its capacity to emit fewer harmful gases. Gas emissions were measured using a plastic chamber connected to a uniTOX instrument, and litter moisture was assessed using AOAC methods.ResultsBy days 21, 28, and 35, the moisture levels in the HS and HS + P groups were significantly lower (p < 0.001) compared to the C group. HS maintained a slightly acidic pH in the experimental groups, whereas the C group’s pH became slightly alkaline. The absorption properties of HS and pH stabilization contributed to the rise in NH3 and CO2 emissions to the environment at a lower rate than in the C group (p > 0.05). The second aim was to monitor the influence of HS and P as feed and litter additives on bacterial counts and the antimicrobial resistance of E. coli isolates by the microdilution method. Coliform and fecal coliform counts were significantly lower (p < 0.001) in the litter of the experimental groups on day 35. Minimum inhibitory concentration revealed resistance to ciprofloxacin, tetracycline, ampicillin + sulbactam, and cotrimoxazole among E. coli isolates, with resistance ranging from 5 to 15% across all groups.DiscussionIt is concluded that the effect of the additives used increased litter quality. These findings underscore the importance of incorporating additives into intensive poultry systems, where maintaining litter quality is crucial to reducing disease transmission, improving animal welfare, and increasing production efficiency.